Escoramento de laje treliçada utilizando a linguagem de programação dynamo - Lopes, Lucas Figueiredo (2022)
One of the main problems regarding the shoring of lattice slabs is the spacing between their lines that serve as support for the joists. This dimensioning, according to Torres (2018, p.16) lacks in-depth studies on the subject. Thus, the works of Sartorti (2013, 2016) can be used to calculate this spacing, using the bearing capacity of the joists, the normative requirements and allied to the automation technology of BIM projects and gain productivity and security in the elaboration of a project. of shoring. With these studies on the resistant efforts of trussed joists, the matrix method of displacements was used for the structural analysis of the joist, with combinations of actions in the construction phase. The structural analysis and design algorithm was done in Python while the slab recognition and line drawing code was done in Dynamo. The results comparing a TR 12645 truss with another TR 16745, for the same 6m span, an increase in the spacing of the joist lines can be seen with the increase of the height of the truss and the diameter of the upper chord, generating savings and efficiency.